Assessment of thermo-oxidative induced chemical strain by inverse analysis of shrinkage profiles in unidirectional composites. (1st December 2016) - Gigliotti, M.; Minervino, M.; Lafarie-Frenot, M.C.
Abstract: The present paper focuses on the assessment of thermo-oxidative induced chemical strain in HTS/TACTIX carbon/epoxy Organic Matrix Composites for High Temperature Applications, by inverse analysis of shrinkage profiles in unidirectional composites. First, measurement of matrix shrinkage in composites surface is carried out by Interferometric Microscopy for virgin samples (initial state) and for samples aged under oxygen pressure and air at atmospheric pressure: then, a model based on thermodynamics with Internal Variables and ABAQUS numerical simulations carried out on unidirectional composite realistic samples are employed for inverse identification of thermo-oxidative induced chemical strain and its evolution during conditioning. The identification is performed successfully and validated against chemical shrinkage profiles developing in pure resin systems. The model is then used for calculating thermo-oxidative induced stresses related to chemical shrinkage inelastic strains and for the prediction of the observed fibre/matrix debonding scenario. A Rayleigh-Ritz method is also developed for rapid prediction of matrix shrinkage in composite materials.